Tanzende Wandervögel auf der Wiese (1920)
soziale Fragen;Kultur und Religion;Kunst;Bühnenkünste politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung soziale Fragen;Leben in der Gesellschaft (allgemein);Freizeit